Influence of microscopic features on self cleaning ability of textile fabrics - Atwah, Ayat Adnan; Khan, Muhammad A. (SAGE, 2022)
In the presented review, the past investigations have been complied and critically analyzed to highlight the influence of microscopic features on self-cleaning ability. In addition, challenges and research gaps that currently exist are discussed. This review concludes the current methods and processes to obtain self-cleaning ability using the surface features of textile fabrics manipulated with the help of the coatings and nanoparticles. However, no research was conducted to explore the self-cleaning potential of microscopic geometrical features of fabric at the woven structural level.
Keywords: Self-cleaning ability; textile fabrics; surface coating; nanotechnology; influence; microscopic features